(untitled) (Kronika Bydgoska, 2010)
Doctor Stefan Turowski (1919-2000), a historian, headmaster, academic teacher, and social activist. A graduate of the Nicolaus Copemicus Univer- sity in Toruń. The author of the work “German minority in Pomerania Region in the years 1920-1923”. In 1971, after the doctoral examination at the NCU he was awarded the academic degree of doctor of the humanities based on his doctoral thesis “The policy of the Polish authorities towards the German minority in Pomorskie Voivodeship in the years 1932-1939”. During the Nazi occupation, he was taken away to forced labour in Bavaria as an agricultural worker. Starting from October 1945, he was employed as the head of the Education Department in Wąbrzeźno and Golub-Dobrzyń, in the years 1961-1981 - the head and headmaster of the Primary Schools No. 12 and No. 61 in Bydgoszcz, and in the years 1978-1992 - an academic teacher in the WSP Higher Teacher Education School in Bydgoszcz. An eminent teacher and educator of young people. The author of the work “The United Evangelical Church in Poland 1920-1939” and co-author of several histori- cal monographs. An active member and activist of the Polish Scouting Association, Bydgoszcz Scientific Association, and the Friends of Bydgoszcz Association.